Where elephants roam: perceived risk, vulnerability, and adaptation in the Okavango Delta - Lauren Redmore (Resilience Alliance, 2020)
Where people and elephants share space, the chance of human-elephant interactions (HEI) shape how people make livelihood decisions, including where and when to harvest resources. In the Eastern Panhandle of the Okavango Delta in Botswana, elephant populations have doubled in the past 10 years. Currently 16,000 men and women from different ethnic backgrounds share woodlands with 18,000 elephants. People carry out livelihoods in ways that are shaped by multiple facets of their identities, including gender, age, ability, and ethnicity. Residents depend on firewood for energy, but collecting firewood where elephants may be is risky because elephants can kill people. Using an intersectional approach, we asked how do facets of people's identities influence perceived risk, ability to adapt, and vulnerability to HEI? We conducted one year of mixed method, ethnographic research in the village of Mokgacha in the Eastern Panhandle. We found that both men and women collected elephant-felled firewood but had different perceptions of risk to HEI and adapted in different ways. Women often harvested in groups and the middle of the day, whereas men harvested alone in the morning and evenings while tending to cattle, leaving them vulnerable to elephants. Because of physical limitations, the elderly and people with disabilities were vulnerable to HEI and relied on resource sharing from family to reduce their vulnerability to HEI. Settlement history also influenced how people of different ethnicities are vulnerable because of access to environments with low visibility and higher chance of HEI. This work provides insights on who, how, and when people adapt to minimize the potential danger of HEI when collecting firewood. To reduce unwanted HEI and ensure continued support for elephants by rural residents, conservation interests should focus efforts on building solutions that recognize social diversity, recognize local perceptions of risk, and reinforce culturally relevant adaptations.